Efektivitas Metode Simulasi Total Physical Response pada Praktik Terbang Pre Solo - Agung Wahyu Wicaksono; Stephen Huibert Daniel Agu; Arya Yuda Prawira (Politeknik Penerbangan Jayapura, 2025)
Pilot training is a complex and demanding process, especially in the pre-solo phase where student pilots must master various technical and non-technical skills before being allowed to fly solo. One potential method to use is the Total Physical Response (TPR) method, which at the Indonesian Civil Pilot Academy of Banyuwangi is often referred to as